Islamic education for disabilities: new model for developing Islamic parenting in Integrated Blind Orphanage of Aisyiyah - Choirul Mahfud; Imam Rohani; Zalik Nuryana; Munawir Munawir; M. Baihaqi (IAIN Salatiga, 2023)
This study proposes Islamic education for disabilities as a new way of developingan Islamic parenting model applied at the integrated blind orphanages of AisyiyahPonorogo, Indonesia. This research method is a qualitative study using in-depthinterview techniques, participant observation, documentation, and content analysis. This study found that the Islamic parenting model applied at the Aisyiyah Ponorogo is more dominated by authoritative parenting styles than permissiveand authoritarian parenting. This finding confirms criticism and a solutionto Baumrind’s parenting theory on the one hand. It means that the design ofauthoritative and Islamic parenting is more helpful in producing a parentingstyle oriented towards a more positive aspect, achieving, independent, religious,responsible, and closer to the child’s future. The Islamic-based parenting modelapplies the parental model of flexibility and adaptability involving some aspects ofparenting style, work program, paradigm, method, and instrument. The research’ssignificance is to understand the Islamic parenting model applied to integratedblind orphanages of Aisyiyah Ponorogo that can be used as role models for otherorphanages throughout Indonesia. The current research brings value and can beused as a lesson learned for other Muslim communities in Indonesia.